Kisah Pengasuhan Maryam Dalam Al-Qur’an Perspektif Semiotika Roland Barthes - Saputri, Yosi Rani; Alfadilah, Alfadilah; Faizin, Faizin; Hadi, Syofyan (Ikhtisar: Jurnal Pengetahuan Islam, 2023)
This research aims to reveal Maryam's parenting pattern in the Qur'an using Roland Barthes' semiotic approach. This research is motivated by the discovery in the Qur'an of a female figure who is so special that her name is immortalized in one surah in the Qur'an, namely surah Maryam. This certainly doesn't happen by itself, of course there is a process of nurturing and education that makes Maryam special. This research uses qualitative methods with library research. This research data analysis uses Roland Barthes' semiotic theory with three stages, namely denotation, connotation and myth. The results found in research using Roland Barthes' three stages of semiotics found several parenting patterns in QS Ali- Imran verses 33-44: First, parenting starts from a pious family. Second, obeying Allah during the pregnancy process. Third, giving the best name to child. Fourth, pray that children will be protected from the temptations of Satan. Fifth, provide the best and quality education. Sixth. Parenting must be done seriously and to the fullest. Seventh, providing food that is halal and good. Eighth, good parenting must be carried out by pious people.